Hubungan Antara Perceived Social Isolation dengan Social Disconnection Pada Generasi Z - Kumalasari Indah Cahya Ningsih; Erik Saut Hatoguan Hutahaean; Ferdy Muzzamil (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the relationship between perceived social isolation and social disconnection among Generation Z. Generation Z is a generation that grew up in a digital ecosystem and relies heavily on social media in their social lives. The digital paradox experienced by this generation raises questions about the relationship between feelings of social isolation and actual social disconnection. This study employed a quantitative approach with a correlational design. The sample consisted of 160 respondents selected using purposive sampling technique. Instruments used were the UCLA Loneliness Scale (Version 3) to measure perceived social isolation and the Social Disconnection Scale (SDS) to measure social disconnection. Hypothesis testing was conducted using Pearson Product Moment correlation. Results showed a significant positive relationship between perceived social isolation and social disconnection (r = 0.848; p < 0.001). Most respondents were in the moderate category on both variables, with a considerable proportion in the high category, particularly for social disconnection. These findings indicate that the higher the perceived social isolation felt by Gen Z individuals, the higher their level of social disconnection, even though they are digitally active.